2015
DOI: 10.1007/s10853-015-9153-3
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale modeling of sensory properties of Co–Ni–Al shape memory particles embedded in an Al metal matrix

Abstract: The concept of utilizing ferromagnetic shape memory alloys as embedded sensory particles in aluminum alloys for damage detection is discussed. When embedded in a material, a shape memory particle can undergo an acoustically detectable solid-state phase transformation when the local strain reaches a critical value. The emitted acoustic signal can be used for real-time damage detection. To study the transition behavior of the sensory particle inside a metal matrix under load, a simulation approach based on a cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…We utilized the parallel MC code developed by V. Yamakov at NASA. 58,59 Two MC modes were implemented in this work: the semi-grand canonical ensemble and the composition-controlled algorithm.…”
mentioning
confidence: 99%
“…We utilized the parallel MC code developed by V. Yamakov at NASA. 58,59 Two MC modes were implemented in this work: the semi-grand canonical ensemble and the composition-controlled algorithm.…”
mentioning
confidence: 99%
“…Such a material design approach is considered promising to confer self-healing features to metallic alloys [7]. Alternative concepts involve acoustic or magnetic detection of the martensitic transformation of such embedded shapememory particles to facilitate damage detection [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In the past three decades, Housler based magnetic controlled shape memory alloys (MCMEA), such as Ni-Mn-Ga [1,2], Co-Ni-Ga [3,4], Ni-Fe-Ga [5,6], Ni-Mn-X (X = In, Sb, Al) [7,8], and Co-Ni-Al [9,10], have attracted much scientific attention as it concerns the sensors and actuators industry. These kinds of Housler alloys are characterized by the ability of creating a large magnetic field induced strain (MFIS) and their high response frequency under an external magnetic field (EMF) [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, recent studies [10,14,15] on Co-Ni-Al series alloys, revealed that a large output MFIS could be affected by two main parameters, including a suitable martensite structure and a large deformation drive force. As it concerns the first factor, the MFIS can be obtained due to the martensite twin boundaries rearrangement under EMF.…”
Section: Introductionmentioning
confidence: 99%